The supervisory encounter and the senior GP trainee: managing for, through and with. Issue 2 (16th October 2017) - Brown, James; Nestel, Debra; Clement, Tim; Goldszmidt, Mark
Abstract : Objective: Help‐seeking supervisory encounters provide important learning experiences for trainees preparing for independent practice. Although there is a body of expert opinion and theories on how supervisor encounters should happen, supporting empirical data are limited. This is particularly true for the senior general practice (GP) trainee. Without knowing what happens during these encounters, we cannot know how to maximise their educational potential. This study aimed to understand what happens when senior GP trainees call on their supervisor when caring for patients and how learning can be enhanced when this occurs. Methods: This is an analysis of data from a multi‐case study of five GP supervisory pairs, each with a GP registrar and their supervisor. The data are recordings of 45 supervisory encounters, 78 post‐encounter reflections and six interviews. We used Wenger's communities of practice theory and rhetorical genre theory as analytical lenses. Results: The supervisory encounters followed a consistent format, which fitted the form of a genre. Within this genre, three dominant interactional patterns were identified, which we labelled 'managing for', 'managing through' and 'managing with'. Each pattern presented different opportunities and drew on different skills. The primary agenda was always developing a plan for the patient. Education agendas included acquiring knowledge, developing skills and achieving independence. Other agendas were issues of control, credibility and relationship building. Both supervisor and trainee could be purposeful in their supervisory engagement. Conclusions: For supervisors and trainees to achieve the educational potential of their supervisory encounters they require flexibility. This depends on understanding the genre of the supervisory encounter, the agendas at play, the options they have in engaging and having the skills to utilise these options. Educators can facilitate supervisors and trainees in acquiring this understanding and these skills. We recommend further research into the genre of the supervisory encounter. Abstract : The authors demonstrate a consistent structure to supervisory encounters, within this are identifiable patterns that achieve different things. By understanding the structure, supervisors and trainees can achieve more with their encounters